Assistance in the Provision of Clean Water and Sanitation Facilities and Infrastructure in Kalisat Village, Kalisat District, Jember Regency - Akbar Maulana, Akbar Maulana; Suyono, Suyono; Sukoco, Sampir Andrean (Universitas Muhammadiyah Jember, 2024)
The assistance programme for the provision of clean water and sanitation facilities and infrastructure in Kalisat Village, Kalisat Sub-district, Jember Regency aims to improve the quality of life of the village community through better access to clean water and sanitation facilities. This assistance involves various stages, starting from the initial survey to identify needs and environmental conditions, planning, to the implementation of the necessary infrastructure. Active community participation is a key component of the programme, supported by training and education on the importance of sanitation and hygiene. Collaboration with the local government and related agencies also played an important role in the success of the programme. The results of the programme showed increased access to clean water for villagers as well as improved sanitation conditions, which directly contributed to a decrease in the incidence of diseases associated with poor water and sanitation. In addition, community awareness about the importance of maintaining environmental hygiene has also increased. With this success, the mentoring programme in Kalisat Village is expected to become a model that can be applied in other villages in an effort to improve access to clean water and sanitation that is sustainable and environmentally sound